"A body in transformation"—An empirical phenomenological study about fear‐avoidance beliefs towards physical activity among persons experiencing moderate‐to‐severe rheumatic pain. Issue 1 (1st August 2018) - Lööf, Helena; Johansson, Unn‐Britt
Abstract: Aims and objectives: To gain a better understanding of fear‐avoidance beliefs towards physical activity and body awareness in people experiencing moderate‐to‐severe rheumatic pain. Background: Rheumatoid arthritis and psoriatic arthritis are long‐term conditions with pain as the prominent symptom. Health‐promoting physical activity is recommended and can have an analgesic effect. High self‐rated pain has previously been reported to be associated with increased fear‐avoidance behaviour in relation to physical activity. Body awareness, which includes attentional focus and awareness of internal body sensations, could be valuable in the nursing care of long‐term diseases. Design: Empirical phenomenological. Methods: An empirical phenomenological psychological method was applied. The interviews took place between autumn 2016–spring 2017 with 11 informants (eight women and three men, age range 44–71 years) who were diagnosed with rheumatoid arthritis ( n  = 7) or psoriatic arthritis ( n  = 4), with a disease duration ranging from 3–35 years. The mean visual analogue scale score in the study sample was 60 mm. Results: Three typologies were identified: "My relatively fragile physical status", "I am an active creator" and "Part of something bigger than myself." Conclusions: The current findings indicated that pain anticipation and fear‐avoidance beliefs towards physical activity sometimes affected the behaviour of individuals with long‐term rheumatic pain syndromes. People experiencing moderate‐to‐severe rheumatic pain tended to focus on their fragile physical and emotional state. By adopting a more favourable attitude towards the self, the body could be restored to a state of calm and balance. Relevance to clinical practice: The current findings are relevant for healthcare professionals engaged in health‐promotion clinical practice.